Efecto de la temperatura de colada sobre la dureza, desgaste y fluidez de la aleación asm 356, colada en molde de arena en forma de espiral - Mantilla Castañeda, Jorge Eduardo (2016)
The effect of the casting temperature on the hardness, wear resistance and flowability or coliability of the ASM 356 aluminum alloy has been studied. Casting temperatures of 680, 700, 750 and 800 ° C were considered. The hardness test was performed according to ASTM E-140, the wear resistance test was performed according to ASTM G-77, and for the flowability or coliability test the specimen was spiral according to the Chneider method, cast in sand mold. According to the results obtained show that the hardness decreases with the increase of the casting temperature from 95.30 HB to 680 ° C to 81.50 HB for 800 ° C and the wear resistance also decreases as the casting temperature increases because with the Increase in temperature, the grain size grows in the structure, making it less compact. And in terms of fluidity or coliability measured in centimeters, this increases with the increase in casting temperature because of the increase in overheating by delaying nucleation and the greater volume of fluid passing through the channel as the temperature of wash. It is observed that the microstructure for all casting temperature levels consists of thin and flat plates of acicular form of magnesium - silicon (Mg2Si) and aluminum - silicon eutectic that grows slightly as the casting temperature increases. According to the statistical analysis with a confidence level of 95%, it is observed that the casting temperature significantly affects the hardness, wear resistance and fluidity or coliability of the ASM 356 alloy